تبديل الوسوم المتعدد البروتوكولات (MPLS) - أحمد, أحمد صقر; دندة, رضوان; جعفر, منهل (Latakia University Journal -Engineering Sciences Series, 2019)
مع النمو المتسارع لشبكة الإنترنت توجب على التكنولوجيا التكيف بثبات مع المتطلبات الجديدة لعرض الحزمة المتزايد, فبالإضافة إلى الخدمات المزودة في الوقت الحالي فقد طورت ونشرت خدمات جديدة, مما أثقل كاهل البنية التحتية الحالية للإنترنت بمصطلحات السرعة وعرض الحزمة , ومع تطبيق النسخة السادسة من بروتوكول الإنترنت (IPv6) بدا التنافس بين حوامل ومزودات الخدمة ظاهراً من حيث البحث عن طرق توجيه فعالة وسريعة لرزم البيانات مع ضمان جودة الخدمة (QoS: Quality of Service) وصنف الخدمة (Cos: Class of Service) وتأمين إدارة وهندسة الحركة على الشبكة (Traffic Engineering) بالإضافة إلى دعم الشبكات الافتراضية الخاصة (VPN's: Virtual Private Network's ). وظهر تبديل الوسوم المتعدد البروتوكولات ( MPLS: Multi Protocol Label Switching ) كتقنية معيارية حديثة تفي المتطلبات السابقة بعدما كانت هي في البداية طريقة لتحسين سرعة إرسال الموجهات . تزودنا هذه الدراسة بنظرة معمقة على التقنية الموجودة خلف MPLS ومكوناتها وآلية عملها وتطبيقاتها. As the Internet growing at a high pace, the technology has had to adapt constantly to new demands for increased bandwidth. In addition to the traditional services currently provided, new services have been developed and deployed, which have strained the resource of the existing Internet infrastructure. Moreover, with the implementation of Internet protocol version 6 (IPv6), carriers and service providers struggle to find efficient and speedy methods to forward packets and provide guaranty for quality of service (QoS), class of service (CoS), traffic engineering, and support virtual private network's (VPN's). MPLS, which at the beginning was a way to enhance the speed of router's forwarding, emerged as a new standard technology to provide the above-mentioned services. This study provides a detailed analysis of the existing technology behind MPLS and its components, mechanism and applications.